Atlas of clinically important Fungi - Sciortino, Carmen V. (John Wiley & Sons, 2017)
Although there are many texts that provide quality information for the identification of fungi, researchers and technologists rarely have time to read the text. Most are rushed for time and seek morphological information that helps guide them to the identification of fungi.